Can behavioural theories explain the initial return of Malaysian IPOs? / Fen Nee Chong - Fen, Nee Chong (Research Management Institute (RMI), 2011)
This paper investigated the impact of behavioural biases on the initial returns ofMalaysian IPOs from the perspectives of divergence of opinion and representative heuristics theories. The initial returns were calculated using 142 IPO samples listed on the Main Board of Bursa Malaysia (formerly known as Kuala Lumpur Stock Exchange). In addition to the behavioural proxies, ex-ante variables were included as control variables in the models for analysis. The findings showed support for initial underpricing of66.51%. Behavioural biases, divergence ofopinion and representative heuristics, were found to have significant explanatory powers over initial returns. The findings fit well with the profile of the Malaysian market whereby the majority of the investors are individuals who are not well-informed and have an emerging market status.